On the rate of convergence of hermite-fejér polynomials to functions of bounded variation on the zeros of certain jacobi polynomials (1990)
In this paper, we study the Hermite-Fejér interpolation, Hn(f,x), for a function f of bounded variation on [-1,1] when the inter)olation is taken over the zeros of Jacobi polynomials, Pn (∝,β ) (x) when |∝|, | β| ≤ ½.Our main result is an estimate for the rate of convergence of Hn(f,x) at points of continuity of f,and a special attention is given to the interpolation over the zeros of the Legendre polynomials.